1975
DOI: 10.1021/bi00679a032
|View full text |Cite
|
Sign up to set email alerts
|

Lipid biosynthesis in sebaceous glands. Regulation of the synthesis of n- and branched fatty acids by malonyl-coenzyme A decarboxylase

Abstract: Crude cell-free extracts isolated from the uropygial glands of goose catalyzed the carboxylation of propionyl-CoA but not acetyl-CoA. However, a partially purified preparation catalyzed the carboxylation of both substrates and the characteristics of this carboxylase were similar to those reported for chicken liver carboxylase. The Km and Vmax for the carboxylation of either acetyl-CoA or propionyl-CoA were 1.5 times 10- minus-5 M and 0.8 mumol per min per mg, respectively. In the crude extracts an inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It seems therefore impossible to speculate that they derive these compounds from the diet unless we learn more about their feeding ecology. A few studies have shown that birds can synthesize some of these compounds de novo via several pathways to produce even and odd numbered, and branched acids and alcohols (Buckner & Kolattukudy 1975;Buckner et al 1978;Hiremath et al 1992;Kolattukudy & Rogers 1987). Thus it appears probable that birds have evolved to produce different mixtures to arrive at similar types compounds to perform similar types of functions in response to the ectosymbionts they encounter, but the organisms may be different for different species.…”
Section: Resultsmentioning
confidence: 99%
“…It seems therefore impossible to speculate that they derive these compounds from the diet unless we learn more about their feeding ecology. A few studies have shown that birds can synthesize some of these compounds de novo via several pathways to produce even and odd numbered, and branched acids and alcohols (Buckner & Kolattukudy 1975;Buckner et al 1978;Hiremath et al 1992;Kolattukudy & Rogers 1987). Thus it appears probable that birds have evolved to produce different mixtures to arrive at similar types compounds to perform similar types of functions in response to the ectosymbionts they encounter, but the organisms may be different for different species.…”
Section: Resultsmentioning
confidence: 99%
“…Methylmalonyl-CoA is an intermediate of propionate metabolism. It can be formed through carboxylation of propionyl-CoA either in the mitochondrial matrix or in the cytosol through the action of propionyl-CoA carboxylase and acetyl-CoA carboxylase (Buckner & Kolattukudy, 1975) respectively. Translocation of the propionyl and methylmalonyl moieties across the mitochondrial inner membrane can be achieved through the formation and transport of their respective carnitine esters.…”
Section: Discussionmentioning
confidence: 99%
“…A novel mechanism for controlling the supply of alternate substrates has been described for the uropygial gland of the goose (32,33). Cell-free extracts from this gland catalyze the carboxylation of propionyl-CoA but not of acetyl-CoA, yet a partially purified preparation carboxylates both substrates.…”
Section: Eukaryotesmentioning
confidence: 99%